A Study of Air Pollution in Kabul City and its Relationship with Climate Change (Salam International Academic Journal, 2023)
Air pollution has severe consequences for human health, particularly on the respiratory system, and its impact on climate change is unmistakable. Over the past decade, the air quality in Kabul city, especially during winters, has deteriorated significantly. This has led to fatalities, particularly among children and the elderly, and has exacerbated climate change. The primary source of air pollution in Kabul city stems from the emission of greenhouse gases resulting from human activities.This research focuses on quantifying air pollution in Kabul city, specifically in terms of greenhouse gas emissions such as sulfur dioxide (SO2), nitrous oxide (N2O), methane (CH4), and carbon dioxide (CO2) across three sectors: energy, industry, agriculture, and livestock, during the years 2012, 2013, and 2014. The calculations were performed using the IPCC-2006 software. The findings reveal that during the winter season, the emission of sulfur dioxide exceeded 0.164 parts per million (PPM), and carbon dioxide emissions reached 56,656.22 gigagrams in 2013, signifying an increase primarily attributed to the energy production sector and fossil fuel consumption. Additionally, the levels of particulate matter (PM2.5 and PM10) in the air exceeded 35 micrograms per cubic meter in summer, spring, and fall.To mitigate its serious impacts, several measures are recommended, including promoting green spaces, restricting the import of low-quality fuel, implementing effective air pollution management, raising environmental awareness among the public, encouraging civic cooperation in maintaining the cleanliness of Kabul city, improving traffic management, and implementing proper waste disposal practices. The study's findings underscore the noticeable climate change trends in Kabul city over the past decade, driven by rising temperatures and increased energy demand. Consequently, it is imperative for authorities and relevant organizations to develop a comprehensive plan to combat air pollution, curb the consumption of fossil fuels, and heed the serious warning presented by these results.
Keywords: Air pollution; PM2.5; PM10; fossil fuels; greenhouse gases